Distinct Roles of α7 nAChRs in Antigen-Presenting Cells and CD4+ T Cells in the Regulation of T Cell Differentiation - Mashimo, Masato; Komori, Masayo; Matsui, Yuriko Y.; Murase, Mami X.; Fujii, Takeshi; Takeshima, Shiori; Okuyama, Hiromi; Ono, Shiro; Moriwaki, Yasuhiro; Misawa, Hidemi; Kawashima, Koichiro (Frontiers in Immunology, 2019)
Abstract It is now apparent that immune cells express a functional cholinergic system and that α7 nicotinic acetylcholine receptors (α7 nAChRs) are involved in regulating T cell differentiation and the synthesis of antigen-specific antibodies and proinflammatory cytokines. Here, we investigated the specific function α7 nAChRs on T cells and antigen presenting cells (APCs) by testing the effect of GTS-21, a selective α7 nAChR agonist, on differentiation of CD4+ T cells from ovalbumin (OVA)-specific TCR transgenic DO11.10 mice activated with OVA or OVA peptide323-339 (OVAp). GTS-21 suppressed OVA-induced antigen processing-dependent development of CD4+ regulatory T cells (Tregs) and effector T cells (Th1, Th2 and Th17). By contrast, GTS-21 up-regulated OVAp-induced antigen processing-independent development of CD4+ Tregs and effector T cells. GTS-21 also suppressed production of IL-2, IFN-, IL-4, IL-17, and IL-6 during OVA-induced activation but, with the exception IL-2, enhanced their production during OVAp-induced activation. In addition, during antigen-nonspecific, APC-independent anti-CD3/CD28 antibody-induced CD4+ polyclonal T cell activation in the presence of respective polarizing cytokines, GTS-21 promoted development of all lineages, which indicates that GTS-21 also acts via α7 nAChRs on T cells. These results suggest 1) that α7 nAChRs on APCs suppress CD4+ T cell activation by interfering with antigen presentation through inhibition of antigen processing; 2) that α7 nAChRs on CD4+ T cells up-regulate development of Tregs and effector T cells; and that α7 nAChR agonists and antagonists could be potentially useful agents for immune response modulation and enhancement.